EDUKASI MODERASI BERAGAMA SEJAK DINI PADA ANAK DI TADIKA AL-FIKH ORCHARD-MALAYSIA - Zuliana, Zuliana; Qorib, Muhammad; Wirian, Oktrigana; Butlam, Qoree (CV. Lafadz Jaya, 2024)
This study aims to understand religious moderation education for early childhood at Tadika Al-Fikh Orchard Malaysia. The research uses a qualitative method with data collection techniques of observation, interviews, and documentation. The data analysis used is the Miles and Huberman model, which includes data reduction, display, and verification. The results show that early religious moderation education is needed to prevent children's behavior that does not align with religious teachings in the educational environment. The education is carried out by instilling awareness about religious diversity, teaching the values of religious tolerance, using engaging learning media, conducting practical religious moderation activities in the classroom, and encouraging parental participation. Strengthening religious moderation in early childhood includes four aspects of religious moderation: instilling national commitment, strengthening tolerance, anti-violence, and introducing and preserving local culture. Strengthening religious moderation needs to be taught to children from an early age so that they can develop moderate traits from a young age.